Gambaran Pengetahuan dan Sikap dalam Kesiapan Tenaga Kesehatan Terhadap Manajemen Bencana Di Rumah Sakit Arun Lhokseumawe - Manurung, Fakhri Bonatua; Utariningsih, Wheny; Fauzan, Ahmad (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2025)
Disasters are events that can disrupt community activities and welfare. In dealing with disasters, effective management is very dependent on the readiness of health workers, which includes aspects of knowledge and attitude. This research aims to describe the level of knowledge and attitudes of health workers in preparedness for disaster management at Arun Lhokseumawe Hospital. The research method used is descriptive with a cross-sectional approach. The sample consisted of 70 respondents selected using a stratified random sampling technique based on the Slovin formula. Data collection was carried out through a structured questionnaire that measured the level of knowledge and attitudes of health workers towards disaster management. The results showed that the majority of health workers had a good level of knowledge (61.4%), while 32.9% had sufficient knowledge, and 5.7% had insufficient knowledge. In terms of attitude, 98.6% of respondents showed a positive attitude, while only 1.4% had a negative attitude. It is hoped that health workers can maintain and improve their readiness through ongoing training held by relevant agencies to strengthen understanding and preparedness in facing disasters in health service facilities.